Representasi Bullying dalam Film “Anyone Anywhere” Menggunakan Analisis Semiotika Charles Sanders Peirce - Ade Leasfita; Laurencia Goliesman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The school environment should be a safe place for children. However, in reality, it is one of the places where bullying occurs, as in the short film